Influence of unmodified and modified nanoclay content on mechanical and thermal properties of the waste polyolefin - Yusoh, K.; Abdullah, Norhayati; Ghazali, Suriati (2018)
The aim of this research (waste to wealth), is to study the improved thermal and mechanical properties of waste polypropylene (wPP) in a nanocomposite. For this purpose, Organo-modified (OMMT) and unmodified sodium montmorillonite clay (MMT) were employed to fabricate polypropylene/clay nanocomposite. Commercial grade (OMMT) and (MMT) were added in a range of 1-5 wt %, in wPP to prepare polypropylene-clay nanocomposites, following the melt intercalation method. Fourier transform infrared spectroscopy (FTIR) and Field Emission Scanning Electron Microscope (FESEM) were used to evaluate polymer structure before and after the fabrication. Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) were used to analyse the thermal stability and thermal properties for the waste polyolefin and respective nanocomposites. The FTIR and FESEM results exhibited no change in the chemical structure of the polymer after clay addition and no exfoliation was observed in case of unmodified clay. Melting temperature and crystallization percentage was increased up to 3 wt% loading which was the best in comparison to the original waste matrix. The thermal stability of the wPP/clay nanocomposites was found improved in the case of loading 3 wt % of OMMT.